Hilfst du mir, so hilfst du dir. Diplomatische Überzeugungsstrategien der Regentin Christine Charlotte von Ostfriesland (reg. 1665–1690) gegenüber Kaiser Leopold I. - Rieke Becker (Österreichische Zeitschrift für Geschichtswissenschaften)
The article focuses on the state diplomacy of the regent Christine Charlotte from the perspective of New Diplomatic History and informed by a cultural-historical approach. It analyses the patterns of argumentation and rhetorical strategies she used to persuade the emperor to support her in the domestic power struggle with the East Frisian estates. She used her inferior, weak position and asymmetrical relationship with the emperor as a strong argument to engage Leopold I on a moral level. Moreover, by rhetorically transforming her own problems into those of the emperor and the empire as a whole, she turned Leopold’s support into the emperor’s own interest on a rational level.